School Based Management: Decision Making by Student Representatives at MAS Al-Washliyyah 22 Tembung - Pradita, Syakila; Nasution, Inom (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the role of student representatives in decision-making within the framework of School-Based Management (SBM) at MAS Al-Washliyyah 22 Tembung, located in Medan, North Sumatra, Indonesia. Using a qualitative case study approach, data were collected through observation, interviews, and document analysis. Participants included two student representatives, three teachers, and two students selected purposively to represent diverse perspectives. The findings reveal that student representatives play a significant role in promoting exemplary leadership, facilitating effective communication between stakeholders, and providing inclusive spaces for discussion. These three aspects are fundamental in supporting collaborative decision-making and ensuring that student voices are meaningfully integrated into school governance. The presence of structured mechanisms such as Standard Operating Procedures (SOPs) further enhances the effectiveness and transparency of student-related decisions. This research contributes to a deeper understanding of participatory leadership practices in religious educational institutions and highlights the importance of empowering students in shaping a more democratic and responsive school environment. It is recommended that other madrasahs consider formalizing student participation in decision-making to foster school improvement and student engagement.